Investigation of some characteristics of enzymes that ensure the process of membrane digestion in paddlefish and Russian sturgeon - A. N. Nevalennyy; D. A. Bednyakov; V. Yr. Novinskiy (Юг России: экология, развитие, 2015)
Complex research of characteristics of some enzymes which are carrying out membrane hydrolysis of food at a spoonbilled cat and Russian sturgeon is carried out. High thermostability enzymes the squirrel of all investigated enzymes is marked.